ECONOMIC EFFICIENCY CAN BE ACHIEVED THROUGH BIOFARMING (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article examined the effectiveness of organic farming. Moreover, analytical data on international experience, problems, including opportunities for science and modern approaches in the field of food safety, digitalization and production technologies are considered.